Analysis of Covid-19 Pandemic Data According to the Countries Including in the Human Development Index by Using Clustering Analysis K-Average Method - Kanberoglu, Zafer; görür, çetin; yıldırımçakar, ibrahim; türkmenoğlu, mustafa (International Journal of Contemporary Economics and Administrative Sciences, 2021)
One of the important disasters of the 21st century is the Covid-19 epidemic that started in China in December 2019 and spread all over the world in a short time. The Covid-19 epidemic, which started as a health problem, continues to deeply affect all structures of the countries with its economic and social dimensions. Although there is a parallelism between the development level of the country and its success in combating the epidemic, differentiation is observed from time to time. Within the scope of this study, Covid-19 epidemic data will be obtained by country and will be analyzed using the Cluster analysis K-Average Method. The sample of the study will be forty countries in total, including ten countries in eachcategory, in different developmentcategories in the United Nations human development index. In the first stage of the cluster analysis to be used in the study, the variables of total cases, daily cases, total deaths and daily deaths belonging to countries; In these cond phase, total cases per million, daily cases per million, total deaths per million and deaths per million will be used. It will be analyzed whether the variables used in the said stages make a meaningful clustering. In this context, it will be revealed whether countries are in the same cluster according to their level of development in the fight against the Covid-19 epidemic.